Sculpting a Life : Chana Orloff between Paris and Tel Aviv - Birnbaum, Paula (Book collections on Project MUSE., 2023)
"The first biography of sculptor Chana Orloff, and the first to include stories from her unpublished "memoir," which focus on the artist's early life in Ukraine, her family's move to Palestine and Orloff's life there (1905-1910), and her subsequent years between Paris and Tel Aviv"--